Teknik Guru Kelas Dalam Menangani Siswa Trouble Maker Di Madrasah Ibtidaiyah Miftahul Ulum Sidowungu - Sonia; Nur Hudah (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2021)
In class learning activities do not always run smoothly and conducive, there are obstacles. One of the obstacles to learning in the classroom is the presence of trouble makers. Trouble maker students are students who make problems or who behave disruptively. Examples of the behavior of trouble maker students at Madrasah Ibtidaiyah Miftahul Ulum Sidowungu include disturbing other students, often going in and out of class, not paying attention to the teacher delivering subject matter, using cleaning tools to play, arguing when advised by the teacher, playing a role as a champion in class, and don't want to do the job. Therefore, the teacher must have a way to deal with the behavior of the trouble maker students. Starting from this phenomenon, the researcher wants to know in depth about the techniques and constraints of classroom teachers in dealing with trouble makers students. The research method that the researcher uses is a qualitative method, with a phenomenological approach, by searching for data through interviews, observation and documentation to several data sources, after which data analysis from Miles and Huberman is carried out accompanied by data triangulation. The results showed that the techniques or methods used by classroom teachers in dealing with trouble maker students, among others: finding out the factors causing students to behave in trouble makers, providing assistance and guidance, giving advice, giving punishment and the last one is communicating with students' parents. While the obstacles experienced by classroom teachers in dealing with trouble maker students include: the first is students who are silent when asked so that the teacher has difficulty finding the causal factor, the second is students who always repeat their actions and the last is the lack of support from the parents of students. To follow up on students' trouble makers, teachers continue to provide assistance and guidance and keep in touch with students' parents.